2021
DOI: 10.1002/hyp.14159
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting physical and chemical conditions of two rock glacier springs

Abstract: Rock glaciers are increasingly influencing the hydrology and water chemistry of Alpine catchments. During three consecutive summers (2017-2019), we monitored by recording probes and fortnightly/monthly field campaigns the physical and chemical conditions of two rock glacier springs (ZRG, SRG) in the Zay and Solda/Sulden catchments (Eastern Italian Alps). The springs have contrasting hydrological conditions with ZRG emerging with evident ponding (pond-like), and SRG being a typical high-elevation seep (stream-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…This pattern requires that the sources of water are changing, not just their proportions. Additionally, the maintenance of cold (<1 °C) temperatures in the rock glacier discharge indicates that these systems are thermally buffered throughout the summer, likely due to the presence of internal ice within the rock glacier (Berger et al, 2004;Brighenti et al, 2021a). High values of d-excess in the rock glacier water are consistent with the melting of ice that has undergone multiple freeze-thaw cycles (Steig et al, 1998;Williams et al, 2006).…”
Section: Rock Glacier Water Sourcesmentioning
confidence: 87%
See 1 more Smart Citation
“…This pattern requires that the sources of water are changing, not just their proportions. Additionally, the maintenance of cold (<1 °C) temperatures in the rock glacier discharge indicates that these systems are thermally buffered throughout the summer, likely due to the presence of internal ice within the rock glacier (Berger et al, 2004;Brighenti et al, 2021a). High values of d-excess in the rock glacier water are consistent with the melting of ice that has undergone multiple freeze-thaw cycles (Steig et al, 1998;Williams et al, 2006).…”
Section: Rock Glacier Water Sourcesmentioning
confidence: 87%
“…In a key study to consider multiple years of water chemistry from the same rock glacier springs (Brighenti et al, 2021a), found that patterns of changing EC and hydrochemistry occurred with a similar timing during each melt season, with the magnitude of EC elevation and trace element enrichment corresponding with the date when snowmelt ended and with peak summer temperatures. In this regard it is notable that at the Chepeta SNOTEL site near RG-1 and RG-2, peak snow water equivalent (SWE) was nearly identical in the spring of 2021 (270 mm) and the spring of 2022 (287 mm), therefore although the exact date when snowmelt ended each year is FIGURE 8 Schematic diagram illustrating how the time series of water samples collected in the Uinta and La Sal Mountains are used to address 3 complementary questions.…”
Section: Interannual Variabilitymentioning
confidence: 99%
“…In the last decades, the hydraulic behavior of frozen layers has been defined mainly by studying the response of the rock glaciers springs to geochemical tracers (e.g., stable isotopes of hydrogen and oxygen, electrical conductivity and radionuclides e.g., Krainer et al, 2007;Brighenti et al, 2021). Therefore, the most interesting result of this infiltration experiment with ERT time-lapse measurements is that negative resistivity variations, related to the injected water flow, are almost negligible inside the detected frozen layer.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the hydraulic behavior of rock glaciers and their impact on the hydrology of alpine catchments are relatively less defined (Pauritsch et al, 2017). The hydrological and the geochemical monitoring of spring waters emerging downslope of active rock glaciers have been used to investigate runoff processes and the presence and role of frozen layers in alpine catchments (e.g., Krainer et al, 2007;Carturan et al, 2016;Brighenti et al, 2021). In active or ice-rich intact rock glaciers, continuous frozen layers are typically considered as aquicludes (Giardino et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that a waveletbased approach is suitable for investigating hydrological data (Graf et al, 2014;Fang et al, 2015;Weigand et al, 2017). It has been applied to detail transit times, and in more limited scope used in hydrochemistry/biogeochemical studies, for example on temporal changes of dissolved elements in glacier springs and karst springs or forested areas (Weigand et al, 2017;Brighenti et al, 2021;Rezaei and Saatsaz, 2021). However, its application is (still) limited by the fact that the method is rather "data hungry" (Lloyd et al, 2014).…”
Section: Introductionmentioning
confidence: 99%